TELAAH KEBIJAKAN SIBER TIONGKOK DAN PENGARUHNYA TERHADAP PERUSAHAAN TEKNOLOGI AMERIKA SERIKAT - Safitri, Siti Alifiyah; Hasymi, Aditya Maulana (CONVERGENCE: JOURNAL OF GLOBAL DYNAMICS, 2025)
This research explores the establishment of the Cyberspace Administration of China (CAC) as a strategic response by the Chinese government to counter the influence of American technology companies in the digital sphere. Employing a descriptive qualitative method and grounded in Digital Sovereignty and Cyberpower theories, this study analyzes the role of CAC as a central instrument in managing digital governance and national information control. Findings reveal that CAC serves not only as an administrative authority but also as a political apparatus designed to ensure ideological conformity, protect national data, and promote digital independence. Through strict regulations and censorship, CAC imposes operational limitations on U.S.-based tech firms like Google, Facebook, Apple, and Microsoft. These actions align with China’s broader ambition to establish cyber sovereignty, safeguard national security, and ensure domestic political stability. By analyzing CAC’s institutional design and policy implementation, this research contributes to understanding how authoritarian states leverage digital governance to challenge Western technological dominance and reshape global internet governance norms.